A simple and sensitive electrochemiluminescence aptasensor for determination of ochratoxin A based on a nicking endonuclease-powered DNA walking machine. (1st June 2019) - Wei, Min; Wang, Chunlei; Xu, Ensheng; Chen, Jin; Xu, Xiaolin; Wei, Wei; Liu, Songqin
Highlights: Low background was obtained by efficiently ECL-RET between CdS QDs and Cy5. Nb.BbvCI worked effectively to release Cy5-DNA from electrode in the presence of OTA. DNA walking machine improved the sensitivity of the aptasensor obviously. The aptasensor is selective, reliable, and could be employed in real samples. Abstract: Ochratoxin A (OTA) poses a serious threat to the health of human beings and animals. In this paper, a simple and sensitive electrochemiluminescence (ECL) aptasensor was constructed to detect OTA based on electrochemiluminescence resonance energy transfer (ECL-RET) and a nicking endonuclease-powered DNA walking machine. Originally, the signal of cadmium sulfide semiconductor quantum dots (CdS QDs) was quenched efficiently by Cy5. After the addition of OTA, the walker autonomously hybridized with Cy5-labeled DNA and released plenty of Cy5-DNA from the electrode surface with the help of a nicking endonuclease. As a result, the signal of CdS QDs recovered efficiently. As an artificial and popular signal amplification technique, the DNA walking machine greatly improved the sensitivity. Under optimal conditions, the aptasensor not only detected OTA in a linear range from 0.05 nM to 5 nM with a detection limit of 0.012 nM (S/N = 3), but also showed an excellent selectivity for OTA over other mycotoxins.